1977
DOI: 10.1007/bf02015075
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy and epifluorescence investigation of bacterial colonization of marine sand sediments

Abstract: Scanning electron microscopy (SEM) was employed for the investigation of microorganisms living in marine sand sediments. Epifluorescence, as well as sediment analyses, gave further data on the parameters of the sediment samples.SEM revealed a correlation between the site and density of bacterial colonization and the microtopography of the individual sand grains.Sand grains with a medium roundness showed the greatest density of bacterial colonization. Protected surface sites were favored in the colonization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 7 publications
6
50
0
Order By: Relevance
“…Differences in the composition of the in situ bacterial community and the bacterial community used as a tracer may influence grazing rate estimates because of selection for specific size classes (Epstein & Shiaris 1992a, Hahn & Höfle 1999 and/or species (Pérez-Uz 1996). Perhaps more important is the consideration that bacteria in sediments are mostly associated with sediment and detrital particles (Weisse & Rheinheimer 1978). Several flagellate species show marked preferences for attached and aggregated bacteria (Caron 1987, Sibbald & Albright 1988, so FLB should therefore be prepared from natural assemblages of free and attached bacteria.…”
Section: Abstract: Bacterivory · Heterotrophic Flagellates · Grazingmentioning
confidence: 99%
“…Differences in the composition of the in situ bacterial community and the bacterial community used as a tracer may influence grazing rate estimates because of selection for specific size classes (Epstein & Shiaris 1992a, Hahn & Höfle 1999 and/or species (Pérez-Uz 1996). Perhaps more important is the consideration that bacteria in sediments are mostly associated with sediment and detrital particles (Weisse & Rheinheimer 1978). Several flagellate species show marked preferences for attached and aggregated bacteria (Caron 1987, Sibbald & Albright 1988, so FLB should therefore be prepared from natural assemblages of free and attached bacteria.…”
Section: Abstract: Bacterivory · Heterotrophic Flagellates · Grazingmentioning
confidence: 99%
“…Factors influencing the distribution of microbes in sediments include sediment grain size and shape (Meadows & Anderson 1967, Weise & Rheinheimer 1978, Nickels et al 1981, Hoppe 1984, Mayer et al 1985, carbon content (Cammen 1982, DeFlaun & Mayer 1983, Yamamoto & Lopez 1985, fluid flux to the bed (Thistle et al 1984, Eckman 1985, sediment disturbance (Wainright 1987, Findlay et al 1990a) and animal-microbe interactions (Federle et al 1983, Aller & Yingst 1985, Dobbs & Guckert 1988, Reichardt 1988, Findlay et al 1990b. Of these, the first 3 are most likely to influence microbial colonization of freshly deposited, abiotic sediments.…”
Section: Microbial Colonization Of Sedimentsmentioning
confidence: 99%
“…Bacteria and microalgae concentrate in areas of low relief, i.e, surface fissures, crevices, cleavage ledges and concave abrasions (Meadows & Anderson 1967, Weise & Rheinheimer 1978, Nickels et al 1981, Hoppe 1984, Mayer et al 1985, and total microbial biomass tends to be higher on grains with more surface Irregularities. Smooth grains, while supporting fewer procaryotes and microalgae, tend to support larger popul a t i o n~ of microeucaryotic grazers (Nickels et al 1981) Microbial community structure Just as the amount of phospholipid phosphate can be related to the total microbial biomass present in a sample, the amount the individual phospholipid fatty acids can be related to the biomass of specific groups of microorganisms that contain the individual fatty aclds (for a current revlew see Vestal & White 1989; for a detalled discussion of the interpretation of PLFA profiles see Findlay & Dobbs in press).…”
Section: Microbial Colonization Ratesmentioning
confidence: 99%
“…If time in transport (to the particle pool of interest) is a significant fraction of the microbial population doubling time, microbial abundance could increase through reproduction on, or immigration to, the transporting particle. The concentrations of microbes in particle crevices and recesses (Meadows and Anderson 1968;Weise and Rheinheimer 1978;DeFlaun and Mayer 1983) suggest that particle collisions affect microbe distribution and abundance. Steele (1976) reported that the strong swash action at an exposed Indian beach removes much of the epipsammic production.…”
Section: Methods and Resultsmentioning
confidence: 99%